NILAI-NILAI BUDAYA PADA TRADISI ACARA POTANG BALIMAU MASYARAKAT MELAYU DI KECAMATAN UJUNGBATU - Rupiana; Wimbrayadi (Universitas Negeri Padang, 2025)
This research aims to describe the values contained in the Balimau Potang traditional event in the Malay community of Ujung Batu District. This type of research is qualitative with a descriptive analytic method. The instruments for this research are the researcher themselves, supported by writing tools, a flash drive and a camera. Data collection techniques include literature study, observation, interviews, and documentation. The steps in data analysis are data collection, data reduction, and drawing conclusions. The research results show that the Balimau Potang tradition in Ujung Batu District contains various important values that reflect the richness of culture and the social life of the community. The cultural values of the Balimau Potang event tradition are a blend of spiritual, ethical, moral, norms, and customs. The spiritual values in this tradition foster a spirit of self-purification in the lead-up to Ramadan. Balimau reflects a symbol of repentance and inner and outer cleansing that strengthens the relationship between humans and God. Moral and ethical values teach the importance of maintaining good behaviour, courtesy, especially when gathering together for religious and cultural activities. The social normative values of balimau reinforce the community's adherence to religious and social norms, such as dressing modestly, respecting elders and community leaders, and maintaining order during events. The values of togetherness and mutual cooperation in the potang balimau event illustrate the solidarity of the community through collective participation in preparing the event, both physically and spiritually, reflecting local wisdom and the spirit of unity. The values of customs in this tradition embody the preservation of local culture that is passed down through generations. Cultural values are reflected in the implementation of professions, the use of regional languages, performing arts, and the active role of cultural figures (ninic mamak).